Genomic analysis of red-tide water bloomed with Heterosigma akashiwo in Geoje - Kang, Hye-Eun (PeerJ, 2018)
Microbial community structures of harmful algal bloom (HAB) caused by Heterosigma akashiwo in Geoje were analyzed using the MiSeq platform. To analyze phytoplankton communities without cross-reactivity with predominant bacteria, a new phytoplankton-specific 23S universal primer set was designed by modifying two previously used ones. The new universal primer set turned out to be a useful tool for the analysis of the phytoplankton community; it showed a high specificity for phytoplankton without cross-reactivity to bacterial sequences as well as the wide taxon coverage presenting from prokaryotic cyanobacteria to eukaryotic algae. Next Generation Sequencing (NGS) data generated by two universal primer sets (16S and 23S) provided useful information about the H. akashiwo bloom. According to the 23S universal primer set, proportions of H. akashiwo increased by more than 200-fold as the bloom occurred and its numbers were high enough to detect in control sites. Its operational taxonomic units (OTUs) were detected in the bloom sites at low proportions suggesting that the 16S universal primer set may not be as effective for monitoring harmful algal blooming (HAB) as the 23S universal primer set. In addition, several abundant OTUs in Chlorophyta were not presented by the 16S universal primer set in this study. However, the 16S primer set was useful for detecting decreases in Foraminifera as HAB occurred suggesting that genomic analyses using two universal primer sets would provide more reliable data for understanding microbial community changes by various environmental or ecological events, including HAB. Genomic analyses using two universal primer sets was also useful for determining a correlation between microbial components as HAB occurred. Heterosigma akashiwo was positively correlated with other bloom species, including Karenia mikimotoi, Teleaulax amphioxeia, and bacteria in Verrucomicrobia.